Comparison of serum sodium and potassium levels in patients with cataract and individuals without cataract in a tertiary care center in North Kerala: a cross-sectional study - H., Rohitha; N. V., Latha; Jacob, Shamin; K. K., Praveena (International Journal of Research in Medical Sciences, 2026)
Background: Cataract remains a leading cause of treatable blindness worldwide, accounting for moderate to severe vision impairment or blindness in approximately 94 million people globally. The study aimed to compare serum sodium and potassium levels between individuals with and without cataract and to assess whether these electrolyte levels vary among the different types of senile cataract classified according to the LOCS III (lens opacities classification system III) classification. Methods: A cross-sectional observational study was conducted on 200 patients aged 50-60 years attending the ophthalmology OPD at a tertiary care center from 2022 to 2024. Cataracts were graded after dilated fundus examination. Serum sodium and potassium levels were measured using ion-selective electrode technology (Beckman Coulter AU-5800). Statistical analysis included descriptive tools and Student’s t-test to assess differences between means. Results: Mean serum sodium was higher in the cataract group (139.3 mEq/l) compared to the non-cataract group (136.6 mEq/l). Serum potassium was also slightly higher in the cataract group, though not statistically significant. Among cataract types, posterior subcapsular cataract showed the highest serum sodium levels. Nuclear sclerosis cases had marginally higher potassium levels than other types, but the difference was not significant. Conclusions: Serum sodium levels were significantly higher in patients with cataract, though still within the normal range. This suggests that dietary sodium restriction might help delay cataract development.